2016
DOI: 10.1111/1742-6723.12590
|View full text |Cite
|
Sign up to set email alerts
|

REACTED – Reducing Acute Chest pain Time in the ED: A prospective pre‐/post‐interventional cohort study, stratifying risk using early cardiac multi‐markers, probably increases discharges safely

Abstract: Paired cardiac markers performed adequately for avoidable MACE, and disposition improved significantly. A confounding system change meant the reduced EDLOS (primary outcome) was unable to be associated with the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…[2][3][4]6,7 Second, LoS in the ED in our study are very short, ranging from 2.9 hours with ruleout based on a hsTnT less than LoD to 5.3 hours with the 0/3-hour diagnostic algorithm. In the literature, reported LoS vary between 4 hours, 8,26 5.3 hours, 38 5.5 hours, 39 6.4 hours 19 to 26.3 hours, 31 with the shortest observation times (median LoS 4 hours in both studies) using the dual biomarker strategy, 8 or the 0/1-hour rule-out in the TRAPID study. 26 Conversely, the longest LoS have been reported in an Australasian cohort, 31 in which LoS was associated with high utilisation rates of investigations before discharge.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[2][3][4]6,7 Second, LoS in the ED in our study are very short, ranging from 2.9 hours with ruleout based on a hsTnT less than LoD to 5.3 hours with the 0/3-hour diagnostic algorithm. In the literature, reported LoS vary between 4 hours, 8,26 5.3 hours, 38 5.5 hours, 39 6.4 hours 19 to 26.3 hours, 31 with the shortest observation times (median LoS 4 hours in both studies) using the dual biomarker strategy, 8 or the 0/1-hour rule-out in the TRAPID study. 26 Conversely, the longest LoS have been reported in an Australasian cohort, 31 in which LoS was associated with high utilisation rates of investigations before discharge.…”
Section: Discussionmentioning
confidence: 91%
“…Third, post-implementation discharge rates after ruleout were 62.8% and thus at the upper end of the reported range. Discharge rates in other observational or randomised studies are heterogeneous with low discharge rates among low-risk patients between 18.4% and 26%, 9,18,21 intermediate discharge rates between 42.3% and 55% 19,39,40 and high discharge rates between 67.8% and 72%. 8,38,41 Only one study 42 reported significantly longer hospitalisation stays by 35%, fewer early discharges after a negative result (7% vs. 22%, P=0.0001), more coronary angiograms (77% vs. 55%, P=0.0001) and revascularisations (45% vs. 31%, P=0.0001) after implementation of hsTn assays by 35%.…”
Section: Discussionmentioning
confidence: 98%
“…To date, the reported literature on sex differences in triage categorisation in those presenting with chest pain has been inconsistent,9 13 with most focusing on its late management 14. Further, it is uncertain whether, among individuals who present with chest pain, delay in time to medical examination is associated with increased in-hospital mortality, and if so if this differs by sex.…”
Section: Introductionmentioning
confidence: 99%